(untitled) (Theatrum historiae, 2008)
The article deals with the development of attitudes to monasteries, regulars and nuns that can be observed in the minds of the members of baroque society (1650-1750) and of the leaders of intellectual elite in the times of Enlightenment at the end of the 18th century. At the beginning, the author attempts to analyse certain negative „enlightened“ attitudes to regular life in the Habsburg monarchy. He uses several promotional and publicist works showing that damnatory relation to monasteries occured together with the dissolution of monasteries in 1780. The author explains that the attitude of the Enlightenment to regular life was caused by the change of religious life merits. The rationalization of devoutness effected the new view on monasteries – the „enlightened“ people thought that only practical social activities of some monasteries were acceptable. For example, they appreciated the care of the ill, charity activities, education and upbringing of youth, and scientific activities. On the other hand, baroque society highly appreciated religious activities of monasteries, promotion of baroque spirituality among the seculars, and also the regular life as such. The author concludes that, in the Czech lands of the baroque times, we can also find some people who perceived monasteries and their inhabitants in a rather negative way. These opinions created a mental fundament to help in re-interpretation by the „enlightened“ critics of regular life.